2019
DOI: 10.1038/s41598-019-47577-8
|View full text |Cite
|
Sign up to set email alerts
|

Structural and functional microbial diversity along a eutrophication gradient of interconnected lakes undergoing anthropopressure

Abstract: We present the results of an analysis of the 16S rRNA-based taxonomical structure of bacteria together with an analysis of carbon source utilization ability using EcoPlate (Biolog, USA) metabolic fingerprinting assessment against the backdrop of physicochemical parameters in fifteen interconnected lakes. The lakes exhibit a wide spectrum of trophic gradients and undergo different intensities of anthropopressure. Sequences of V3–V4 16S rRNA genes binned by taxonomic assignment to family indicated that bacterial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
48
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 97 publications
(55 citation statements)
references
References 57 publications
6
48
0
1
Order By: Relevance
“…The present study observed significantly higher number of proteobacteria, Actinobacteria, and Cyanobacteria in the estuarine waters of Anjarakkandi river, Dharmadam. Previous studies have indicated that the bacterioplankton belonging to the proteobacteria, Actinobacteria, and Cyanobacteria predominates in the eutrophic waters compared to other bacterial groups (Kiersztyn et al 2019). The increased diversity of these bacteria correlates with the increased level of nitrogenous compounds present in the Anjarakkandi river and possibly an indicative of the eutrophication status of the estuary.…”
Section: Discussionmentioning
confidence: 99%
“…The present study observed significantly higher number of proteobacteria, Actinobacteria, and Cyanobacteria in the estuarine waters of Anjarakkandi river, Dharmadam. Previous studies have indicated that the bacterioplankton belonging to the proteobacteria, Actinobacteria, and Cyanobacteria predominates in the eutrophic waters compared to other bacterial groups (Kiersztyn et al 2019). The increased diversity of these bacteria correlates with the increased level of nitrogenous compounds present in the Anjarakkandi river and possibly an indicative of the eutrophication status of the estuary.…”
Section: Discussionmentioning
confidence: 99%
“…Following this, environmental 46 changes can affect community structure and composition and disrupt vital functions pivotal for 47 ecosystem functioning. Such triggering changes in the abiotic environment may include the 48 use of antibiotics [10], or eutrophication of lake ecosystems [11]. 49…”
Section: Introduction 39mentioning
confidence: 99%
“…Our main contribution is a machine learning-based framework for the quantification of the information shared between the microbiome and a total of 25 physico-chemical and positional (i.e., GPS coordinates and altitude) parameters of an ecosystem. It builds upon a wealth of studies that elucidate the role of the microbiome in ecology using machine learning [19,[31][32][33][34][35][36][37][38][39]. In our framework, a model learns a projection of the microbial prevalence space to a single dimension for each of the parameters, which makes it able to handle the extremely high dimensionality of amplicon-based microbiome datasets.…”
Section: Introductionmentioning
confidence: 99%